Revolutionising corporate governance: blockchain’s transformative impact and potential - Ogedengbe, Fowokemi Alaba; Adelowotan, Micheal Olajide (Frontiers in Blockchain, 2025)
Research question/IssueBlockchain, as a disruptive technology, is reshaping organisational frameworks through its inherent immutability and robust security features. This offers significant potential to enhance corporate governance by fostering more efficient and effective governance models. This paper seeks to (1) critically assess the transformative influence of blockchain technology on corporate governance and (2) propose a “Holistic Governance Synthesis Framework” that identifies and evaluates the features, factors, benefits, risks and impacts of blockchain integration in corporate governance using various theoretical perspectives.Research findings/InsightA thematic analysis of 106 peer-reviewed articles on blockchain and corporate governance was conducted, with dataset retrieved from Web of science and Scopus. Analysis was carried out through manual review of papers and the use of research analysis tools. Analysis tools employed include Microsoft Excel, Harzing Publish or Perish (for data organisation, analysis and thematic coding), VOS viewer and LaTeX (for data visualisation). Identified key themes include critical features (e.g., immutability, smart contract, and traceability), impacts (e.g., investment efficiency, improved firm performance, and audit quality), risks and challenges (e.g., regulatory uncertainty, technical limitation and ethical concerns) associated with blockchain integration in corporate governance are discussed. Based on these emergent themes, conceptual frameworks were proposed to guide future blockchain applications in governance contexts.Theoretical/Academic implicationsTheories such as agency, institutional, stakeholder and transaction-cost economies were used to provide valuable insights for stakeholders. This is aimed at equipping management and shareholders with a nuanced understanding of the internal and external dynamics of blockchain adoption in corporate governance. It also offers implications for institutional bodies to develop regulations that recognize blockchain’s role, thereby enhancing monitoring mechanisms and mitigating associated risks.Practitioner/Policy implicationsThis study offers insight to policymakers by advocating for regulatory frameworks that recognize and guide the integration of disruptive technologies, including blockchain, into corporate governance. Such policies should address the use of digital currencies and blockchain activities, enhancing tax recognition and reducing evasion.